Psychopharmacology in myasthenia gravis patients with focus on depression - Wisnu Wardhana, Ida Bagus Gede; Sri Wahyuni, Anak Ayu; Arimbawa, Komang (International Journal of Research in Medical Sciences, 2019)
Myasthenia gravis is an autoimmune disease with a potential to disrupt brain function and cause depression as a result of the disease itself or treatment side effect. Some biological and psychological mechanisms have been proposed for the correlations between myasthenia gravis and depression. Depression might present in patients myasthenia gravis, and it might complicate the course of the disease. Adequate treatment might not only improve the depression but might also impact the myasthenia gravis in general.